Does the national competency standards framework for pharmacists in Australia support the provision of behaviour change interventions?. (1st June 2021) - Singh, Harjit K; Kennedy, Gerard A.; Stupans, Ieva
Abstract: Issue addressed: Australian pharmacists are increasingly moving towards the provision of patient‐centred professional pharmacy services for chronic disease management. Some of these services are targeted towards improving patients' health and wellbeing through the facilitation of patient‐driven health behaviour change. This paper investigates whether the provision of behaviour change interventions by Australian pharmacists is adequately underpinned by the current competency framework. Methods: The foundation and behaviour change competences within each of the domains in the generic health behaviour change competency framework (GHBC‐CF), was mapped to the Australian pharmacist competency framework. Results: Although the Australian competency framework underpins most of the foundation and behaviour change competences of the GHB‐CF required to undertake low‐intensity interventions, for medium to high‐intensity interventions four specific task‐related competences need to be addressed. These are F12 'Ability to recognise barriers to and facilitators of implementing interventions', BC4 'ability to agree on goals for the intervention', BC5 'capacity to implement behaviour change models in a flexible but coherent manner' and BC6 'capacity to select and skilfully apply most appropriate intervention method'. Conclusion: Additional training is necessary if pharmacists aspire to provide behaviour change interventions for chronic disease management, in particular those that are complex as they involve changes to multiple health behaviours. So what?: The identification of these gaps is critical and can potentially be addressed in postgraduate training programs and as pharmacy curricula are updated.